2019
DOI: 10.1101/574509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Postmortem Cortex Samples Identify Distinct Molecular Subtypes of ALS: Retrotransposon Activation, Oxidative Stress, and Activated Glia

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a fatal neurodegenerative disease characterized by the progressive loss of motor neurons. While several inherited pathogenic mutations have been identified as causative, the vast majority of cases are sporadic with no family history of disease. Thus, for the majority of ALS cases, a specific causal abnormality is not known and the disease may be a product of multiple inter-related pathways contributing to varying degrees in different ALS patients. Using unsupervised machi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 56 publications
0
65
0
Order By: Relevance
“…Notably, the IAP-Gag labelling was not uniform, as some neurons expressed higher levels of IAP-Gag and we found clear evidence of ERV-derived protein aggregation (Fig 6d), suggesting that the expression of ERVs in the brain is associated with aggregation of ERV-derived proteins, which could be the underlying reason of the apparent neuroinflammation. and schizophrenia, where an increased expression of TEs has been reported along with the speculation of their contribution to the disease process (Andrews et al, 2000;Douville et al, 2011;Garson et al, 1998;Guo et al, 2018;Jonsson et al, 2020;Karlsson et al, 2001;Li et al, 2015;MacGowan et al, 2007;Perron et al, 1997;Perron et al, 2008;Steele et al, 2005;Sun et al, 2018;Tam et al, 2019b). However, these studies have been difficult to interpret since the clinical observations were correlative and since the modeling of ERV activation in an experimental setting is challenging.…”
Section: Aggregates Of Erv-derived Proteins Are Found In Areas Of Neumentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the IAP-Gag labelling was not uniform, as some neurons expressed higher levels of IAP-Gag and we found clear evidence of ERV-derived protein aggregation (Fig 6d), suggesting that the expression of ERVs in the brain is associated with aggregation of ERV-derived proteins, which could be the underlying reason of the apparent neuroinflammation. and schizophrenia, where an increased expression of TEs has been reported along with the speculation of their contribution to the disease process (Andrews et al, 2000;Douville et al, 2011;Garson et al, 1998;Guo et al, 2018;Jonsson et al, 2020;Karlsson et al, 2001;Li et al, 2015;MacGowan et al, 2007;Perron et al, 1997;Perron et al, 2008;Steele et al, 2005;Sun et al, 2018;Tam et al, 2019b). However, these studies have been difficult to interpret since the clinical observations were correlative and since the modeling of ERV activation in an experimental setting is challenging.…”
Section: Aggregates Of Erv-derived Proteins Are Found In Areas Of Neumentioning
confidence: 99%
“…However, it is becoming increasingly clear that ERVs are aberrantly activated in various human diseases, including a number of neurological disorders. For example, ERV expression has been found to be elevated in the cerebrospinal fluid and in post-mortem brain biopsies from patients with multiple sclerosis, amyotrophic lateral sclerosis, Alzheimer's disease, Parkinson's disease and schizophrenia (Andrews et al, 2000;Douville et al, 2011;Garson et al, 1998;Guo et al, 2018;Karlsson et al, 2001;Li et al, 2015;MacGowan et al, 2007;Perron et al, 1997;Perron et al, 2008;Steele et al, 2005;Sun et al, 2018;Tam et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…They sequenced the RNAs that were bound to TDP-43 protein in human SH-SY5Y neuroblastoma cells using an enhanced crosslinking and immunoprecipitation protocol (eCLIP-seq) (Van Nostrand et al, 2016), and found that transposable elements accounted for 31% of all mapped peaks. Their data support a model whereby human transposons are normally silenced by TDP-43, but that such silencing is reversed in a subset of ALS patients, which may lead to cellular toxicity (Tam et al, 2019).…”
Section: Frontotemporal Lobar Degeneration (Ftld) and Amyotrophic Latmentioning
confidence: 61%
“…The Hammell lab recently analyzed the transcriptomes of 148 ALS cortex tissue samples and identified three ALS clusters based on the observed gene expression profiles: (1) a major cluster of samples with oxidative and proteotoxic stress (61% of patients), (2) a second cluster with glial activation and inflammation (19% of patients) and (3) a third cluster with retrotransposition reactivation (20% of patients) (Tam et al, 2019). Since oxidative stress and inflammation previously have been implicated in ALS, the investigators focused on the retrotransposon cluster, which included elements from the LINE, SINE, and LTR classes.…”
Section: Frontotemporal Lobar Degeneration (Ftld) and Amyotrophic Latmentioning
confidence: 99%
“…An extensive body of evidence has suggested that glia contribute to the neurodegeneration observed in ALS and FTD (9,10,(110)(111)(112)(113). Transcriptional assessments and proteomic approaches across the ALS/FTD spectrum have reported robust glia signatures and glia protein modules, respectively, emphasizing a glia involvement in inflammation and contribution to disease (109,(113)(114)(115).…”
Section: Discussionmentioning
confidence: 99%